Percutaneous Treatment of Venous Erectile Dysfunction - Hoppe, Hanno; Diehm, Nicholas (Frontiers in Cardiovascular Medicine, 2021)
Erectile dysfunction is a defined as recurring inability to achieve and maintain satisfactory erection for sexual intercourse associated with relevant life impairment. The underlying etiologies may be manifold and complex. Currently, vascular etiologies are highly prevalent especially amongst elderly men. Of special interest, especially venogenic causes are of increasing relevance. Therapeutic options comprise risk factor modification, pharmacotherapy, surgical treatment, and endovascular treatment. Especially endovascular treatment options have recently increased in popularity including transcatheter embolization procedures for veno-occlusive dysfunction.